STUDENTS’ PERCEPTIONS OF CHATGPT AS A TOOL FOR INDEPENDENT LEARNING SUPPORT - Mises B.C. Abineno; Yuninda Anaci Lulan; Paulinus Alexander Satriano; Selvita Eka Eviana Purba (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The advancement of artificial intelligence (AI) technology has driven the use of digital tools such as ChatGPT to support students' independent learning. This study aims to explore students perceptions of using ChatGPT as a learning aid in a Macroeconomics course. The sample was selected using purposive sampling, involving one class of 30 students with prior experience using ChatGPT in their learning process. The research instruments included a closed-ended Likert-scale questionnaire and open-ended questions to capture the cognitive, affective, and conative dimensions of students perceptions. The findings indicate that the majority of students have a positive perception of ChatGPT, particularly in terms of learning readiness, time flexibility, and efficiency in understanding theoretical concepts. However, the highest score was given to the statement emphasizing the crucial role of lecturers in correcting potential misconceptions arising from AI use. While ChatGPT is regarded as useful and flexible, concerns also emerged regarding overdependence, answer accuracy, and the potential decline in critical thinking skills.